2015
DOI: 10.1080/14763141.2015.1084036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time-of-day on static and dynamic balance in recreational athletes

Abstract: The purpose of this study was to investigate the effect of time-of-day (morning vs. afternoon) on static and dynamic balance in recreational athletes. A total of 34 recreational athletes completed the single-leg stance test with or without eyes open, lower quarter Y-balance test, upper quarter Y-balance test, and single-leg landing balance test in a random order in the morning (7:00-10:00 am) and afternoon (3:00-6:00 pm) for two consecutive days. Compared with the morning, participants demonstrated decreased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
2
3
2
2
Order By: Relevance
“…Reduced postural stability ability observed in the early morning hours, disagrees with previous literature 16 , which reported improved balance in the afternoon (15:00 -18:00 h) when compared to the morning (07:00 -10:00 h). However, these results were more pronounced for static balance with minimal time of day effects reported for dynamic balance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Reduced postural stability ability observed in the early morning hours, disagrees with previous literature 16 , which reported improved balance in the afternoon (15:00 -18:00 h) when compared to the morning (07:00 -10:00 h). However, these results were more pronounced for static balance with minimal time of day effects reported for dynamic balance.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the current study and existing research 16 differ to that of previous studies 15,17 However, these significant improvements were only observed in the upper quarter of the SEBT test, with performance improvements translating to only 1% percentage of change, indicating minimal clinical relevance 15,16 . Furthermore, both studies 15,16 used a mixed gender population. It has been hypothesised that women tend to utilize a greater quadriceps dominant pattern of knee control when compared to males 28 .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of these studies, Heinbaugh, Smith, Zhu, Wilson, and Dai [33] applied a dynamic balance test (Y Balance Test) to 34 physically active participants at 7:00-10:00 and 15:00-18:00. They reported that circadian rhythm had a minimal effect on dynamic balance.…”
Section: Discussionmentioning
confidence: 99%
“…1 I.はじめに 高齢者における転倒は,日中のみでなく夜間から早朝 にも多く発生する 1,2) .その原因には不眠症 3) ,起立性 低血圧 4) ,抑鬱 5) などが考えられているが,平衡機能自 体が概日リズムや覚醒状態に依存するという報告も散見 される [6][7][8][9][10][11][12][13][14] .26 時間の睡眠遮断における経時的な重心…”
unclassified